2017
DOI: 10.15226/jnhfs.2017.001101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Nutritive Administration of Carbohydrates and Protein by Foodstuffs on Skeletal Muscle Inflammation and Damage After Acute Endurance Exercise

Abstract: Ingestion of proteins and carbohydrates after exercise is believed to result in an enhancement of regeneration and physical performance after training. Mostly these nutrients are ingested by athletes via whey protein and glucose based shakes. In this study protein and carbohydrates were administrated via a meal. Effects of this meal delivered carbohydrate and protein ingestion directly after acute endurance exercise on skeletal muscle inflammation and damage were investigated. Therefore 16 subjects performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
3
4
1
Order By: Relevance
“…Our observation might be interpreted as an indication that skeletal muscle damage, induced by exercise, is lower after the uptake of protein/carbohydrate combinations. This is in line with the observation of Diel et al [28] and previous described results [14]. Our data also indicate that administration of protein/carbohydrate combinations by food was as effective as administration by shake.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our observation might be interpreted as an indication that skeletal muscle damage, induced by exercise, is lower after the uptake of protein/carbohydrate combinations. This is in line with the observation of Diel et al [28] and previous described results [14]. Our data also indicate that administration of protein/carbohydrate combinations by food was as effective as administration by shake.…”
Section: Discussionsupporting
confidence: 94%
“…It was clearly visible that exercise results in an increase of blood glucose concentrations 20 min after exercise termination. This is in agreement to our previous investigations [28] and confirms observations that moderate exercise increases blood glucose concentrations in healthy non-diabetic persons when a required exercise volume is achieved [34]. As expected, blood glucose concentration after administration of the shake extended a maximum 40 min after ingestion.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…So far, possible pro-recovery effects after training with ALA supplementation have not been described in the literature. Recent investigations have shown that the application of protein carbohydrate combinations counteracts the training induced loss of performance when administered a single application directly after exercise [45,50,51]. This could not be observed in this study for ALA (Fig.…”
Section: Discussioncontrasting
confidence: 58%